Hrm Practices In Banking Sector In India: Exploring the Impact of HRM Practices on Service Quality in the Indian Banking Sector (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Withthe enhanced weight age of services sector to the country’s GDP coupled withgrowing global competition, it has become important to define and measurequality in services (Sarangi, 2007-08). In today’s world of global competition,rendering quality service is a key for success and many experts concur that themost powerful competitive trend currently shaping marketing and businessstrategy is service quality (Abdullah, 2005). Over the last twenty years or so,a great deal of research attention has been devoted to the field of servicequality (Crosby and Stephens, 1987; Silvestro et al., 1990; Cronin and Taylor, 1992; Avkiran, 1994; Brady andRobertson, 2001; Robledo, 2001). Service quality has been discussed in numberof researches and writings (Gronroos, 1982; Lehtinen and Lehtinen, 1982; Lewisand Booms, 1983; Sasser et al.,1978; Bolton and Drew, 1991; Cronin and Taylor, 1992; Teas, 1993; Chumpitaz andPaparoidamis, 2004; Abdullah, 2005; Zeithaml and Bitner, 2004; Kundu and Vora,2004).